Street-centric routing scheme using ant colony optimization-based clustering for bus-based vehicular ad-hoc network. (September 2020) - Khan, Zahid; Fang, Sangsha; Koubaa, Anis; Fan, Pingzhi; Abbas, Fakhar; Farman, Haleem
Abstract: Bus-based Vehicular Ad-hoc Network (VANET) is an excellent solution to cope with the highly dynamic and inconsistent structure of conventional vehicular network. In this paper, an algorithm for Internet of Energy in the context of Bus-based VANET is proposed, i.e., street-centric routing scheme (SCRS) to address the problem of optimal-route and relay-bus selection. Firstly, we propose a multipath routing scheme using probability of street consistency and probability of path consistency. The multipath improves performance concerning packet delivery ratio and end-to-end delay. Secondly, to enhance the packet forwarding, a new relay-bus selection mechanism is introduced by ant colony optimization (ACO)-based clustering. The relay-bus aims to transmit packets to next forwarding relay. Results show that clustering in ACO algorithm improves the relay-bus selection process by decreasing the computational cost, end-to-end delay, and unnecessary beacon messages. Thus, we conclude that the employment of multipath and clustering significantly improves performance of SCRS.